2012
DOI: 10.3390/ijms130910935
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation of in-Shell and Blanched Peanuts Protects against Mycotoxic Fungi and Retains Their Nutraceutical Components during Long-Term Storage

Abstract: Peanut samples were irradiated (0.0, 5.2, 7.2 or 10.0 kGy), stored for a year (room temperature) and examined every three months. Mycotoxic fungi (MF) were detected in non-irradiated blanched peanuts. A dose of 5.2 kGy was found suitable to prevent MF growth in blanched samples. No MF was detected in in-shell peanuts, with or without irradiation. The colors of the control in-shell and blanched samples were, respectively, 44.72 and 60.21 (L *); 25.20 and 20.38 (Chroma); 53.05 and 86.46 (°Hue). The water activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 49 publications
(71 reference statements)
0
18
0
1
Order By: Relevance
“…Total phenolic contents were determined according to the Folin–Ciocalteu colorimetric method described by de Camargo et al (2012). A calibration curve was obtained using gallic acid (0–8.2 μg/mL) as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…Total phenolic contents were determined according to the Folin–Ciocalteu colorimetric method described by de Camargo et al (2012). A calibration curve was obtained using gallic acid (0–8.2 μg/mL) as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant and potential beneficial effects of different sources of proanthocyanidins against human LDL-cholesterol oxidation and proliferation of breast cancer cells has already been reported [12,25,32]. Contamination with mycotoxins remains a concern for different food products such as milk, wheat and peanuts [33][34][35]. However, it is very difficult to avoid this kind of contamination; furthermore, avoidance from consuming this kind of food products is not always possible.…”
Section: Identification and Quantification Of Phenolic Compoundsmentioning
confidence: 99%
“…The capacity of phenolic extracts in scavenging ABTS radical cation by donation of electrons followed the same trend as TPC. The antioxidant potential of whole and dry-blanched peanuts has already been reported [35]; however, only crude phenolics were evaluated and identification of phenolic compounds was not carried out. Furthermore, the antioxidant effect of crude phenolics of peanut skin in bulk oil has also been demonstrated [38].…”
Section: Antioxidant Activities and Reducing Powermentioning
confidence: 99%
“…Concerning dried fruits, the irradiation of peanuts was evaluated by de Camargo and others () who concluded that an irradiation level of 5.2 kGy was suitable to prevent the growth of aflatoxigenic fungi without significantly affecting their polyunsaturated fatty acid and polyphenol contents. This observation agreed with previous data from Chiou and others (), which proved that radiation levels of 2.5 and 5.0 kGy were effective in retarding the growth of A. parasiticus and in reducing the native mold population of peanuts, respectively.…”
Section: Irradiation To Control Mold Growth and Mycotoxinsmentioning
confidence: 99%